Pasteurization Preserves IL-8 in Human Milk - Giorgi, Marilyn V.; Codipilly, Champa N.; Potak, Debra; Heiman, Howard S.; Schanler, Richard J. (Frontiers in Pediatrics, 2018)
Background: Pasteurized donor human milk is an alternative feeding when mothers’ own milk is not available for premature infants. The effects of pasteurization on the host defense properties of human milk are unclear. We investigated the effects of Holder pasteurization on concentrations of anti-inflammatory and pro-inflammatory cytokines in human milk. Objective: To compare concentrations of anti-inflammatory and pro-inflammatory cytokines before and after pasteurization of donor human milk. Study Design: Samples of milk obtained by electric breast pump from postpartum mothers of premature infants were stored at -80°C. At the time of pasteurization, milk samples were thawed and divided into two aliquots. The first aliquot was re-stored at -80°C and the second aliquot was heat-treated at 62.5°C for 30 minutes and then re-stored at -80°C. At the time of batch cytokine analyses samples were thawed rapidly. Results: Most cytokine concentrations declined following pasteurization. The most prevalent cytokine, IL-8, was preserved (89%) following pasteurization. There were no relationships between gestational age, postnatal age of milk collection, duration of milk storage, and the concentrations cytokines. Conclusion: In contrast to most cytokines after pasteurization, IL-8 is preserved or liberated from another compartment. The maintenance of IL-8 in human milk after pasteurization and the partial loss of anti-inflammatory cytokines following pasteurization, suggests that the effects of inflammatory activity in pasteurized human milk should be evaluated. These data may account, in part, for the lesser protective effect on the host of pasteurized donor human milk compared with mother’s own milk. Thus, we support recommendations for the use of pasteurized donor milk but emphasize that the benefits of mother’s own milk are primary.